Analisis Kendala Mahasiswa dalam Penyelesaian Skripsi pada Masa Pandemi Covid-19 - Gema Janura; Ahyanuardi Ahyanuardi (Jurnal Pendidikan Teknik Elektro, 2021)
This study aims to analyze data on student obstacles in completing thesis during the Covid-19 pandemic with the research subject of Padang State University (UNP) students in the 2016/2017 Electrical Engineering Education Study Program. This type of research is descriptive research. Data collection was carried out using a questionnaire or questionnaire using a Likert scale, as for the tests carried out, validity tests, reliability tests, the results of data obtained from 45 statements distributed, the results showed that there were 3 invalid statements with a reliability level of 0.94 and very high category . The data analysis used is a descriptive statistical technique using the average value of the mean, the standard deviation value and to determine how large the data distribution is using a score category of 1 to 5. The results show that student constraints during the Covid-19 pandemic have different category levels in students. for each indicator, in the high category there are: difficulty in writing a thesis by 40 percent, lazy in doing thesis and 40 percent of campus facilities. The students' obstacles in the medium category were: miscommunication by as much, a minimal student network as large, the length of the lecturer's response as large and the lack of student motivation as large. The obstacle for students in the low category is the difficulty of finding data in the field of . It can be concluded that the obstacles experienced by students during the Covid-19 pandemic are different, each individual graduating on time is the desired achievement for every student, if these obstacles can be overcome it will increase graduates in a timely manner.